INDONESIAN ISLAM: A HISTORICAL PERSPECTIVE - Karim, Muhammad Abdul (Universitas Islam Indonesia, 2018)
The existence of Indonesian Islam today is a continuation of historical episodes in the past. The unique position and role of Islam in the construction of the Unitary State of the Republic of Indonesia is something that deserves to be appreciated. Islam has become the important component that shape the fate of archipelago and its people. This paper seeks to explore this unique field through historical analysis on the arrival of Islam in Indonesia, the phenomena of cultural acculturation that occurs in three ways; natural, educational, and institutional, the role of Islam in the national awakening and the contribution of Islam in the formation of the nation's weltanschaung.